The European League for Non-Western Studies and E-learning - Corda, Alessandra; Oomen, Janus; Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
Leiden’s Faculty of Arts invited on May 20th the members of the ELNWS for a workshop on e-learning for Non-Western studies. The aim of the workshop was to take a closer look at the possibilities of e-learning as a means of realizing co-operation between our universities.During our discussions, and looking back on the past academic years, we attempted to position our own academic community on the Internet, in the sense of 'looking for, finding and putting it on, or giving it a location' in the omnipresent Internet.In order to investigate the ways in which e-learning can be used as a tool to stimulate European co-operation within the field of Non-Western studies, Leiden’s Faculty of Arts rewards one initiative between two or more European universities of the ELNWS with financial support.